Measuring the Concept of Civilian Observers Under Philippine Procurement Law Against International Procurement Instruments: A Compability Analysis - Cadapan-Antonio, Myrish T. (Silliman Journal, 2023)
Procurement systems of the world are creating a new world order that propagates the principles of transparency and integrity. The Filipino contribution is a concept of involving civilians in the entire procurement process. Specifically referred to as civilian observers, the presence of these non-governmental and private organizations was originally intended as a transparency measure to monitor the observance of procurement rules throughout the bidding process. This paper presents this unique concept of the Filipino procurement system and measures it against international procurement instruments like the World Trade Organization Government Procurement Agreement, the World Bank Procurement Rules, the Organization for Economic Cooperation and Development Country Models and the United Nations Convention Against Corruption. This comparison is intended to show its compatibility with international norms.